2020
DOI: 10.1128/msphere.00049-20
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Attenuates the Growth of Human Papillomavirus-Positive Epithelial Cells

Abstract: Human papillomaviruses (HPVs) are small, double-stranded DNA viruses that are significant risk factors in the development of cancer, and HPV accounts for approximately 5% of all worldwide cancers. Recent studies using data from The Cancer Genome Atlas (TCGA) have demonstrated that elevated levels of estrogen receptor alpha (ERα) are associated with improved survival in oropharyngeal cancers, and these elevated receptor levels were linked with human papillomavirus-positive cancers (HPV+cancers). There has been … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 65 publications
1
49
0
Order By: Relevance
“…There is significant evidence suggesting that estrogen may serve as a treatment modality in HPV-related lesions and cancers. The HPV18+ cervical cancer cell line, HeLa, is particularly sensitive to estrogen treatment [138][139][140]. Moreover, our laboratory confirmed HeLa estrogen sensitivity and further compared a number of HPV+ and HPV− epithelial cell lines for estrogen sensitivity; it was found that HPV expression confers specific sensitivity to estrogen, both through the expression of the viral LCR, and through expression of the viral oncogenes E6 and E7 [139].…”
Section: Cell Culture-related Evidence For Estrogen As An Hpv Treatmentsupporting
confidence: 59%
See 3 more Smart Citations
“…There is significant evidence suggesting that estrogen may serve as a treatment modality in HPV-related lesions and cancers. The HPV18+ cervical cancer cell line, HeLa, is particularly sensitive to estrogen treatment [138][139][140]. Moreover, our laboratory confirmed HeLa estrogen sensitivity and further compared a number of HPV+ and HPV− epithelial cell lines for estrogen sensitivity; it was found that HPV expression confers specific sensitivity to estrogen, both through the expression of the viral LCR, and through expression of the viral oncogenes E6 and E7 [139].…”
Section: Cell Culture-related Evidence For Estrogen As An Hpv Treatmentsupporting
confidence: 59%
“…The HPV18+ cervical cancer cell line, HeLa, is particularly sensitive to estrogen treatment [138][139][140]. Moreover, our laboratory confirmed HeLa estrogen sensitivity and further compared a number of HPV+ and HPV− epithelial cell lines for estrogen sensitivity; it was found that HPV expression confers specific sensitivity to estrogen, both through the expression of the viral LCR, and through expression of the viral oncogenes E6 and E7 [139]. This sensitivity to estrogen occurred in foreskin, cervical, tonsil, and HNSCC cell lines [139].…”
Section: Cell Culture-related Evidence For Estrogen As An Hpv Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcription Assay. 5 x 10 5 N/Tert-1 cells were plated out on 100-mm 2 plates and transfected 24 hours later with either 1μg HPV16 E2 plasmid and 1μg pTWIST1-Luc, or 1μg pTWIST1-Luc alone using Lipofectamine 3000 (ThermoFisher Scientific) according to the manufacturer's instructions as previously described (73). pTWIST1-luc contains the human promoter and has been described previously (74,75).…”
Section: Differential Expression In Tcga Head and Neck Squamous Cellmentioning
confidence: 99%